2014
DOI: 10.1186/s13073-014-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

Complex host genetics influence the microbiome in inflammatory bowel disease

Abstract: BackgroundHuman genetics and host-associated microbial communities have been associated independently with a wide range of chronic diseases. One of the strongest associations in each case is inflammatory bowel disease (IBD), but disease risk cannot be explained fully by either factor individually. Recent findings point to interactions between host genetics and microbial exposures as important contributors to disease risk in IBD. These include evidence of the partial heritability of the gut microbiota and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
271
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 351 publications
(288 citation statements)
references
References 38 publications
8
271
0
9
Order By: Relevance
“…However, an important additional component of our study design is that we have controlled for host genetics at the species level by obtaining samples from wild and captive individuals within the same species, replicated across two different species (howler and douc). Although this does not control for within-species individual genetic variation that may cause dysbiosis (14), microbiome variation between captive individuals of the same species is smaller than variation between captive and wild individuals from the same species (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an important additional component of our study design is that we have controlled for host genetics at the species level by obtaining samples from wild and captive individuals within the same species, replicated across two different species (howler and douc). Although this does not control for within-species individual genetic variation that may cause dysbiosis (14), microbiome variation between captive individuals of the same species is smaller than variation between captive and wild individuals from the same species (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Specific environmental and genetic factors have been linked to the development of dysbiosis, including antibiotic use, stress, geography, race, host genetics, and diet (13,14). Of these factors, diet, gastrointestinal motility, and medication history most strongly shape the gut microbiome (13,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The first such studies in humans focused on specific genes and pathways, and have identified several significant microbiome-associated variants [41][42][43][44][45]. However, a potential shortcoming of the above studies is that they require previous knowledge of associated genes, and thus cannot discover new associations.…”
Section: Limited Power Of Microbiome Genome Wide Association Studiesmentioning
confidence: 99%
“…[37] and references therein for a comprehensive review). It has also been observed that many mGWAS hits are found near genes associated with complex diseases [24,[27][28][29]31,39,41,[47][48][49][50], and that multiple studies have implicated variants residing in the same genes, though the exact loci differed between studies [11,36,41].…”
Section: Limited Power Of Microbiome Genome Wide Association Studiesmentioning
confidence: 99%
“…For example CD patients have shown increased expression of a tumor necrosis factor ligand TNFSF15, which is a costimulator of T cells and also causes proinflammatory cytokine production. The TNFSF15 ligand shares overlap in receptor function with the closely related TNFSF14, which functions to activate STAT3 signaling in response to pathogenic bacteria [72]. Furthermore, STAT3 is an important effector of T cell differentiation through the binding of the interleukin (IL)-23 receptor and the RAR-related orphan receptor C (RORC), both of which are IBD risk alleles.…”
Section: Genetic and Microbial Interactions In Inflammatory Bowel Dismentioning
confidence: 99%